Doing Family Memory in the Case of Emigration Experience - Žilinskienė, Laima (Vilnius University Open Series, 2020)
This chapter present the importance of memory making in migrant families lives and how emigrants ‘do’ family memory. A representative survey of Lithuanian residents shows that those with emigration experience since 1990 participate in family memory construction more actively. The development of such communicative family memory is family work which demonstrates family solidarity and occurs between and within generations. However, this research shows that gender, age and location influence who is involved in this process with men and younger family members less likely to participate.